2018
DOI: 10.1001/jamaoto.2018.1441
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Artificial Saliva vs Saline Solution on Rate of Suture Degradation in Oropharyngeal Surgery

Abstract: Knowing the association of saliva with suture degradation rates of various suture types may enable oropharyngeal surgeons to select sutures that retain their strength and degrade at an appropriate rate to allow for the effective healing of the wound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…[ 16 ] Another study concluded that PG demonstrated better breaking strength after soaking in physiologic solutions and those with acidic pH, as compared to natural sutures. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Another study concluded that PG demonstrated better breaking strength after soaking in physiologic solutions and those with acidic pH, as compared to natural sutures. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…The type of suture must be carefully selected by the surgeon based on the mechanical requirements, rate of degradation and strength loss, and the anticipated rate of healing. This decision is particularly critical in high-tension closures or in patients with prolonged wound healing, such as in cases of immunosuppression, diabetes, or radiation therapy 9 . Only a few references compare or discuss the properties and quality of absorbable suture materials 12–15 .…”
Section: Discussionmentioning
confidence: 99%
“…Several articles in the literature have commented on the tensile strength of suture materials and their ensuing degradation. One study showed that chromic suture had the lowest breaking force before immersion into artificial saliva solution 9 . An early study conducted by Shaw et al 18 investigated the intraoral median survival values of the gut, polyglycolic acid, and polyglactin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations